U.S. marine salvage assets and capabilities in a maritime disaster : summary of a workshop, September 4-5, 2008, Beckman Center, Irvine, California - Johnson, Peter (Transportation Research Board, 2009)
Maritime commerce is vital to the nations economic health, with about 15 percent of U.S. gross domestic product flowing through its seaports. Approximately one-third of U.S. imports are carried aboard foreign-flag ships calling at the Ports of Los Angeles and Long Beach, California (LA/LB), making this major port complex particularly vulnerable to any significant disruption in vessel traffic. Concerns about homeland security have led to serious consideration of the likelihood and consequences of a terrorist attack on one or more major hubs of maritime trade.
"Organized by Marine Board, sponsored by U.S. Navy, Office of the Supervisor of Salvage and Diving [and others]."
Keywords: Salvage -- United States -- Congresses.; Marine accidents -- United States -- Congresses.; elektronické knihy; electronic books